2013
DOI: 10.1021/mp400199e
|View full text |Cite
|
Sign up to set email alerts
|

Surface Decorated Gold Nanoparticles by Linear and Cyclic Peptides as Molecular Transporters

Abstract: Gold nanoparticles (AuNPs) were synthesized in situ in a green and rapid method from the reaction of reducing linear and cyclic peptides containing tryptophan and lysine residues, (KW)5 and cyclic [KW]5, with an aqueous solution of HAuCl4 and were evaluated as cellular nanodrug delivery systems. The cyclic or linear nature of the peptide was found to determine the morphology and size of the formed peptide-AuNPs and their in vitro molecular transporting efficiency. While cyclic [KW]5-AuNPs formed sponge-like ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
(50 reference statements)
0
35
0
Order By: Relevance
“…47 5 TEM investigations showed that l(KW) 5 -AuNPs formed ball-shaped structures with the diameter size of 900–1000 nm (Figure 16). A large number of l(KW) 5 -AuNPs were found to be in spherical morphologies and in the size range of 4–35 nm.…”
Section: Peptide Nanostructuresmentioning
confidence: 99%
“…47 5 TEM investigations showed that l(KW) 5 -AuNPs formed ball-shaped structures with the diameter size of 900–1000 nm (Figure 16). A large number of l(KW) 5 -AuNPs were found to be in spherical morphologies and in the size range of 4–35 nm.…”
Section: Peptide Nanostructuresmentioning
confidence: 99%
“…CD studies were conducted according to our previously reported method. 40 All experiments on the samples including [W 5 R 4 C] (50 μM, H 2 O), [W 5 R 4 C]–SeNPs (50 μM, H 2 O), and camptothecin (CPT, 5 μM, DMSO) were performed by using a ratio of 10:1 between the carrier and the drug at room temperature. All measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity assay was performed by using SK-OV-3 (5000), HEK-293T (4000), and CCRF-CEM (40 000) cells based on our reported procedure. 40 The only modification was that the old medium was not replaced in the case of CCRF-CEM by treatments. The compounds were added to the old medium instead.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations